Analisis Pola Perilaku Muslimah Gen-Z dalam Memilih Trend Fashion Ditinjau dari Aspek Gaya Berpakaian (Studi pada Mahasiswi Fakultas Ekonomi dan Bisnis Islam IAIN Bone) - Islami, Az-Zahri Dinul; Darwis, Rahma Hidayati; Safar, Jumriani (Universitas Dharmawangsa, 2025)
In the era of globalization, fashion serves not only as a form of self-expression but also as a marker of religious identity, particularly among Generation Z Muslim women. This study aims to examine the behavioral patterns of Gen-Z Muslimahs in selecting fashion trends, focusing on their clothing styles. The research was conducted among female students of the Faculty of Islamic Economics and Business (FEBI) at IAIN Bone, using a descriptive qualitative method through observation, interviews, and documentation. The findings indicate that Gen-Z Muslimahs at FEBI IAIN Bone are selective in their fashion choices, considering aesthetics, comfort, current trends, and compliance with Islamic principles. Influencing factors include cultural, social, personal, and psychological dimensions. While social media acts as a major source of fashion inspiration, its content is filtered in accordance with Islamic values. Additionally, the surrounding environment—family, peers, and campus life—contributes to shaping their preferences. Fashion that aligns with sharia not only enhances self-confidence but also provides a positive medium for self-expression. Nonetheless, the influence of fast-changing trends can lead to consumerist behavior if not properly managed. Therefore, education and awareness are essential in fostering modest, stylish, and sustainable fashion choices. This study contributes to the development of Islamic fashion that resonates with the character and values of Generation Z.